Determinants of Timely Initiation of Breastfeeding among Disadvantaged Ethnic Groups in Midwest Nepal - Sanjel, Keshab; Amatya, Archana (Journal of Nepal Health Research Council, 2019)
Background: Timely initiation of breastfeeding has the potential to prevent 22% of neonatal deaths if breastfed within an hour after birth. Although breastfeeding is almost universal in Nepal, ranges of regional differences in timely initiation of breastfeeding have been documented. The aim of this study was to identify the prevalance and the determinants of early initiation of breastfeeding among disadvantaged ethnic women in Midwest Nepal. Methods: The data was obtained from a household survey of women who had their last child less than one year of age. Descriptive statistics were used to analyze respondents’ demographic, socioeconomic, obstetric and health services related characteristics. Determinants of timely initiation of breastfeeding were assessed using univariate analysis and further evaluated using multivariable logistic regression analysis.Results: Of 362 mothers, 65.5% initiated breastfeeding within one hour of childbirth. Mothers belonging to Tharu ethnic groups (aOR 1.788; 95% CI: 1.014, 3.152), health facility delivery (aOR 3.381; 95% CI: 1.795, 6.369) and mothers who were counseled on breastfeeding during ANC attendance (aOR 2.898; 95% CI: 1.038, 8.096) were more likely to initiate breastfeeding within the first hour of child birth. Conclusions: Almost two in every three mothers had initiated breastfeeding within one hour of childbirth. The factors influencing timely initiation of breastfeeding were Tharu ethnic mothers, health facility delivery and Ante Natal Care counseling. We need to aim at increasing institutional deliveries and counseling during ANC which may increase the early initiation of breastfeeding among disadvantaged ethnic groups. Keywords: Breastfeeding; determinants; Nepal; prevalence; timely initiation